Analysis of Characteristics and Intervention Strategies for Children with Delayed Communication at KB Fatimatuzzahra Sukabumi City - Isnaini, Fatimah Zahra (CV. Chandralia Bintang Pustaka, 2026)
Communication delay or limited verbal expression in early childhood is a significant developmental concern that can affect children’s social interaction, emotional regulation, and future academic readiness. In early childhood education settings, teachers play a crucial role in identifying and addressing communication delays through daily interaction and pedagogical practices. However, empirical qualitative studies focusing on localized early childhood institutions in Indonesia remain limited, particularly those that explore children’s characteristics and contextualized intervention strategies. This study aims to analyze the characteristics of children with delayed communication or minimal verbal expression and to examine the handling strategies implemented by educators at KB Fatimatuzzahra, Sukabumi City. This study employed a qualitative case study design. Data were collected through classroom observations, in-depth interviews with teachers and school administrators, and document analysis of children’s developmental records. The data were analyzed using thematic analysis involving data reduction, coding, and theme development. The findings revealed distinctive characteristics among children with delayed communication, including limited vocabulary, reliance on non-verbal communication, reduced social interaction, and emotional expression through behavior. Intervention strategies applied by teachers included individualized communication stimulation, play-based interaction, collaboration with parents, and referral to professionals when necessary. The study contributes to a deeper understanding of communication delays in early childhood education contexts and highlights the importance of responsive, collaborative, and contextually grounded intervention strategies to support children’s communication development.